The Contribution of Home, Neighbourhood and School Environmental Factors in Explaining Physical Activity among Adolescents. (31st August 2009) - Haerens, Leen; Craeynest, Mietje; Deforche, Benedicte; Maes, Lea; Cardon, Greet; De Bourdeaudhuij, Ilse
Abstract : The present study aimed at investigating the influence of home, neighbourhood and school environmental factors on adolescents' engagement in self-reported extracurricular physical activity and leisure time sports and on MVPA objectively measured by accelerometers. Environmental factors were assessed using questionnaires. Gender specific hierarchical regression analyses were conducted, with demographic variables entered in the first block, and environmental, psychosocial factors and interactions terms entered in the second block. Participation in extracurricular activities at school was positively related to the number of organized activities and the provision of supervision. Perceived accessibility of neighborhood facilities was not related to engagement in leisure time sports, whereas the availability of sedentary and physical activity equipment was. Findings were generally supportive of ecological theories stating that behaviors are influenced by personal and environmental factors that are constantly interacting.